Anticancer Potential of Small-Molecule Inhibitors of Fatty Acid Amide Hydrolase and Monoacylglycerol Lipase - Jaiswal S.; Ayyannan S.R. (My University, 2025)
Recently fatty acid amide hydrolase (FAAH) and monoacylglycerol lipase (MAGL) inhibitors have been in the limelight due to their anticancer potential. Both FAAH and MAGL are the endocannabinoid degrading enzymes that hydrolyze several endogenous ligands, mainly anandamide (AEA) and 2-arachidonic glycerol (2-AG), which regulate various pathophysiological conditions in the body such as emotion, cognition, energy balance, pain sensation, neuroinflammation, and cancer cell proliferation. FAAH and MAGL inhibitors block the metabolism of AEA and 2-AG, increase endogenous levels of fatty acid amides, and exert various therapeutic effects including chronic pain, metabolic disorders, psychoses, nausea and vomiting, depression, and anxiety disorders. FAAH and MAGL are primarily neurotherapeutic targets, but their contribution to various types of carcinomas are significant. Inhibitors of these enzymes either alone or as multitarget agents, or with supra-additive effects show the potential effect in ovarian, breast, prostate, and colorectal cancers. Besides highlighting the role of FAAH and MAGL in cancer progression, this review provides an update on the anticancer capabilities of known and newly discovered FAAH and MAGL inhibitors and also provides further directions to develop FAAH and MAGL inhibitors as new candidates for cancer therapy. © 2021 Wiley-VCH GmbH